Impact of worksite health-promotion programs in hospital admission costs and medical leaves in a sample of brazilian companies - Plopper, Caio (2015)
Worksite health promotion programs have long been adopted as means to improve employees’ health, and many studies report positive economic returns on investments involved. However, studies with better methodology have started to show smaller returns. The aim of this study was to investigate whether characteristics of worksite health programs play a role as predictors of hospital admission spending (in current BRL) and the proportion of medical leaves from April, 2014 through May, 2015, in a non-random sample of companies in Brazil, through partnership with a health ‘big data’ company. A survey on the characteristics of workplace health program was responded by six large Brazilian companies. Data gathered from these six questionnaires (presence and age of health program, its characteristics – inclusion of screening, health education initiatives, link to other company’s programs, program integration with company’s structure and work environment oriented to health promotion - and the adoption of financial incentives for employee adherence), as well as individual data on employee age, gender, type of health plan offered, were used to build a database with over 76,000 individuals. Through multiple regression and stepwise selection of variables, employee’s age was positively associated and the age of health promotion program and premium health plan were negatively associated with hospital admission costs (as expected). Unexpectedly, the inclusion of screening for disease and health education initiatives in the worksite health program were identified as significant positive predictor of hospital admission costs. To avoid misleading inclusion of maternity leaves, the data on medical leaves for male employees were analyzed (available only for two of the companies included, with a total of 18,957 male employees). Analyzing these data through a Z-test for comparing proportions, the company that included in its health promotion program activities aimed at targeting bad health habits (such as smoking and alcohol abuse), diabetes and hypertension control and that adopted incentives for employee adherence had a lower proportion of employees with medical leaves, as compared to a company without those features (also, highly expected results). However, the company with lower medical leave proportion was also the one that adopted screening activities. Sources of threats to internal and external validity of these results are discussed, as well as possible explanations regarding the association in this sample of screening activities and health education for employees with worse health-related outcomes for the companies are discussed. Further well-designed studies with random larger samples are needed to validate those results and possibly improve internal and external validity of these results.